PENDIDIKAN HOLISTIK DALAM PERSPEKTIF HADIST - Taufik Hidayat; Nur Zakiyah; Ibnu Ubay Dillah; Zulkipli Lessy (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
Nowadays, the implementation of Islamic education is considered unsuccessful so that evaluation and improvement are needed. One of the efforts that needs to be done is to improve the teaching and learning of pendidikan agama Islam (PAI) learning by implementing holistic education. This research is a literature-based research, which the researchers collect various data and sources from journals and books related to holistic education in the perspective of Hadith. The results of this study show that holistic education is an effort to develop all the potentials of students including intellectual, emotional, social, spiritual, creative, and physical. In the perspective of the Quran, holistic education refers to the Islamic concept of kaffah which means comprehensive where education should be carried out vertically and horizontally to form the rights of human being. From the perspective of the hadith, holistic education emphasizes good ethics and provides comfort to students in learning.